O Processo de Concessão dos Sistemas de Transporte de Massa na Região Metropolitana do Rio de Janeiro: Implicações na Organização e na Gestão de Transporte de Passageiros - Duarte, Newton Leão (2000)
This study has the propose to describe and analyze the Rio de Janeiro Metropolitan Region mass transport system concession process context, performed by the State Reform Program between 1995 and 1998, and evaluate its implications on regional public transport organization and management model. Its development enhanced three process aspects: the characterization of scenery existing before the change proposal, the substantive analysis of the transport systems concession policy and the consequent new scenery evaluation. Methodology includes bibliographic research, extensive documentation analysis, fact observation and unstructured interviews with administrators and technicians involved in the processo The resuIts show limitations of traditional planing and anaIysis models to support public transport poIicy formuIation, uncertain performance of regional passenger transport systems and the criticaI situation of mass transport systems conforming a propitious time to private management transfer proposaIs. AIso show that the enterprise occurs under the influence of a BIRD financing state reform project, being performed without relevant references in technical community and producing a weak institutional scenery, inadequate to managing the new concession contracts. In despite of in accord with the investment strategies recommended by Transport Mass Plan realized in 1994, there are no available data yet to characterize significant performance tendencies in the recent privatized systems. Are evident, however, the effects of privatization process on disorganization of the metropolitan transport public management model under State responsibility.